IMPROVEMENT OF THE TECHNOLOGY OF MONETARY VALUE OF GREEN AREAS BY USING REMOTE SENSING METHODS - R. Derkulskyi; O.Lets (Zemleustrìj, Kadastr ì Monìtorìng Zemelʹ, 2018)
In this article we proposed two methods for calculation of monetary value of green areas in cities. Tree canopy cover class area multiply by annual carbon dioxide sequestration rates and monetary value of carbon dioxide removal. The default values (the multipliers) of carbon dioxide removal rates for a unit tree cover were derived from average annual carbon sequestration rates by forest ecosystems of Ukraine. Tree canopy cover class area was calculated in this article by using of two different methods: supervised classification of satellite images by ArcGIS (Maximum Likelihood Classification) and i-Tree Canopy application designed by the US Forest Service (USDA Forest Service).